When Active is Passive: Conditional Cash Transfers and Employment Creation in Macedonia - Gerovska Mitev, Maja (European Centre for Social Welfare Policy and Research, Vienna, 2017)
The paper aims to explore aspects related to the extension of the Conditional Cash Transfer (CCT) programme in Macedonia towards supporting young unemployed from households that are social assistance beneficiaries. The programme itself presents a continuum of active labour market efforts that provide direct financial support as a form of activation of the unemployed in the country. In this respect, the paper challenges the role of direct financial transfers (microcredits, self-employment, subsidized employments) in a socio-economic context in which there is low economic growth, a high level of the informal economy and a low educational level of the unemployed workforce. Under such circumstances, providing direct financial transfers, as a form of activation, does not guarantee improved employability, a trained workforce or secure employment. Existing studies also suggest that the application of such measures “must overcome considerable difficulties and obstacles in a region marked by labour informality and unequal access to opportunities” (ECLAC/ILO, 2014). Also, available evidence shows that “improving the labour inclusion of people with low educational levels is a long-term effort in which beneficiaries require constant psychosocial support, and that the difficulties are even greater for women, youth and persons belonging to indigenous peoples” (OAS/ECLAC/ILO, 2011). The paper is organized in three sections. The first section provides details on recent active labour market programmes in Macedonia. The second section presents a conceptual insight into existing conditional cash transfer programmes, and provides evidence about their success in the field of employment. One of these programmes is the recent CCT incentive targeted towards young unemployed from households that are social assistance beneficiaries. The final section provides an overview of potential risks and threats related to the use of CCT and similar financial transfers and presents recommendations for improved targeting of active labour market programmes in the country.
Innovative Approaches in Labour Market Policy and Health and Long-Term Care in Eastern Europe